Climate Parameters for the Tajik-Uzbek Surface Data Base - Lucas Dugerdil; Odile Peyron; Guillemette Ménot; Dilfuza Egamberdieva; Jakhongir Alimov; Suzanne A G Leroy; Eric Garnier; Arkadiusz Nowak; Sébastien Joannin (PANGAEA, 2025)
This dataset contains the climate parameters for each sampling site of the Tajik-Uzbek Surface Data Base (TUSDB). The parameters have been extracted from WorldClim2 (Fick and Hijmans, 2017), except the Aridity Index (AI) which comes from the CGIAR database (Trabucco and Zomer, 2018). The other climate parameters are Mean Annual Air Temperature (MAAT); Mean Annual Precipitation (MAP); Mean Precipitation of Coldest Quarter (MPCOQ); Mean Precipitation of Warm Quarter (MPWAQ); Mean Temperature of the Coldest Quarter (MTCOQ); Mean Temperature of the Warmest Quarter (MTWAQ).
In: Dugerdil, L et al. (2025): Tajik-Uzbek Surface Data Base for modern pollen samples and vegetation plots: calibrations for functional diversity, climate and vegetation reconstructions in the past [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.979582